2013
DOI: 10.1021/pr3009429
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Phosphoproteomic Analysis of Early Alterations in Protein Phosphorylation by 2,3,7,8-Tetrachlorodibenzo-p-dioxin

Abstract: A comprehensive quantitative analysis of changes in protein phosphorylation preceding or accompanying transcriptional activation by 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) in 5L rat hepatoma cells was performed using the SILAC approach. Following exposure of the cells to DMSO or 1 nM TCDD for 0.5 to 2 h, 5648 phosphorylated peptides corresponding to 2156 phosphoproteins were identified. Eight peptides exhibited a statistically significantly altered phosphorylation because of TCDD exposure and 22 showed a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 116 publications
1
4
0
Order By: Relevance
“…Since a significant elevation of IGFBP-4 protein abundance is not observed within the first 4 h of TCDD treatment, alterations in IGF-dependent signal transduction are highly unlikely to occur within this time period. In accord with this, none of the numerous changes in protein phosphorylation identified in the present study was observed in our recent quantitative proteomic analysis of the impact of TCDD on protein phosphorylation which involved exposure of 5L cells to TCDD for maximally 2 h (Schulz et al, 2013). However, fundamental changes in, e.g., AKT-, ERK-and mTOR-dependent signalling are found at later times and potentially impinge on the results obtained in studies using longer periods of TCDD exposure.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Since a significant elevation of IGFBP-4 protein abundance is not observed within the first 4 h of TCDD treatment, alterations in IGF-dependent signal transduction are highly unlikely to occur within this time period. In accord with this, none of the numerous changes in protein phosphorylation identified in the present study was observed in our recent quantitative proteomic analysis of the impact of TCDD on protein phosphorylation which involved exposure of 5L cells to TCDD for maximally 2 h (Schulz et al, 2013). However, fundamental changes in, e.g., AKT-, ERK-and mTOR-dependent signalling are found at later times and potentially impinge on the results obtained in studies using longer periods of TCDD exposure.…”
Section: Discussionsupporting
confidence: 86%
“…Moreover, the cell lines have been used in investigations on the presence of endogenous AhR-ligands in AhR-deficient cells (Roblin et al, 2004), the regulation of the expression of xenobiotic metabolising enzymes (Münzel et al, 2003;Sawaya and Riddick, 2008;Vondrácek et al, 2009), the influence of the AhR and TCDD on microRNA levels (Moffat et al, 2007) and on the function of the AhR in the activation of oestrogen receptor-dependent transcription by 3-methylcholanthrene (Shipley and Waxman, 2006). We recently characterised the effects of TCDD on the proteome (Sarioglu et al, 2006(Sarioglu et al, , 2008 and early protein phosphorylation (Schulz et al, 2013) in 5L cells. In addition, 5L cells have been proven very useful for studying target genes of the AhR, leading, e.g., to the identification of the cyclin/cyclin-dependent kinase inhibitor p27 Kip1 (Kolluri et al, 1999) and N-myristoyltransferase 2 (Kolluri et al, 2001) as transcriptional targets of the AhR.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the hypothesis, Dong et al [36] reported that the acute TCDD nongenomic pathways could be converted into stable and long-term signals via the activation of several kinases, such as Src kinase and PKA. Notably, a recent study identified a series of proteins that exhibited altered phosphorylation status within 2 h after TCDD exposure, suggesting the existence of dynamic alterations in protein phosphorylation via nongenomic actions [37]. In the study, we showed that TAK1, a crucial kinase involved in acute inflammation in astrocytes, was rapidly phosphorylated and collocated with astrocytes following TCDD exposure [38,39].…”
Section: Discussionmentioning
confidence: 63%
“…Limited studies have utilized LC-MS/MS based methods for the analysis of contaminant induced changes in phosphorylation in mammalian models and include an analysis of rat hepatoma cells exposed to 2,3,7,8-tetrachlorodibenzo-p-dioxin 12 , an analysis of oral administration of the environmental contaminant perfluorododecanoic acid in rat liver 13 , the effect of a mycotoxin on phosphorylation of proteins involved in innate immune responses in the mouse spleen 31 , and the modulation of arsenic toxicity to human kidney cells exposed to selenium 11 . To our knowledge, this is one of few studies to examine rapid changes in phosphorylation after such a brief exposure in vivo other than the study by Pan et al .…”
Section: Discussionmentioning
confidence: 99%